2022
DOI: 10.25217/ji.v7i1.2191
|View full text |Cite
|
Sign up to set email alerts
|

Using of Students’ Modules and Role on Learning Achievement in Covid-19 Pandemic

Abstract: The article explored the relationship between the use of teaching materials and the role of students with learning achievement during the COVID-19 period. The research was correlational quantitative approach with research subjects at the Mechanical Engineering Vocational School. Collecting data using interviews, documentation, and questionnaires. Pearson Product Moment correlation technique analysis, t-test, and F test, with SPSS software. The results showed that the use of teaching materials is an external fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(12 reference statements)
0
0
0
Order By: Relevance
“…E-module in distance learning during COVID-19 enhanced students' achievement in their learning [63]. In addition, another study [64] proved that e-module fosters students' learning via online learning. Besides that, Zoom cloud meeting platform found that it increased students' performance [65].…”
Section: The Evaluation Of Student's Performancementioning
confidence: 99%
“…E-module in distance learning during COVID-19 enhanced students' achievement in their learning [63]. In addition, another study [64] proved that e-module fosters students' learning via online learning. Besides that, Zoom cloud meeting platform found that it increased students' performance [65].…”
Section: The Evaluation Of Student's Performancementioning
confidence: 99%